2021
DOI: 10.3389/fimmu.2021.727161
|View full text |Cite
|
Sign up to set email alerts
|

Mice Plasmacytoid Dendritic Cells Were Activated by Lipopolysaccharides Through Toll-Like Receptor 4/Myeloid Differentiation Factor 2

Abstract: Plasmacytoid dendritic cells (pDCs) are known to respond to viral infections. However, the activation of pDCs by bacterial components such as lipopolysaccharides (LPS) has not been well studied. Here, we found that pDCs, conventional dendritic cells (cDCs), and B cells express high levels of toll-like receptor 4 (TLR4), a receptor for LPS. Moreover, LPS could effectively bind to not only cDCs but also pDCs and B cells. Intraperitoneal administration of LPS promoted activation of splenic pDCs and cDCs. LPS trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The abundance of DCs was significantly positively correlated with the abundance of T cells and cytotoxic lymphocytes in tumor tissues ( Supplementary Figures S5A, B ), partly validating the findings of the scRNA sequencing data analysis. The subpopulation of cells with high expression of BIRC3 was involved in tumor suppressive regulatory role ( Andersen et al, 2017 ; Nakamizo et al, 2021 ), while IRF7 recruited activated inflammatory cells producing interferons ( Tomasello et al, 2018 ; Zhang et al, 2021d ; Somebang et al, 2021 ). Paradoxically, MAT2A and SOX4 were highly expressed in this cluster.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of DCs was significantly positively correlated with the abundance of T cells and cytotoxic lymphocytes in tumor tissues ( Supplementary Figures S5A, B ), partly validating the findings of the scRNA sequencing data analysis. The subpopulation of cells with high expression of BIRC3 was involved in tumor suppressive regulatory role ( Andersen et al, 2017 ; Nakamizo et al, 2021 ), while IRF7 recruited activated inflammatory cells producing interferons ( Tomasello et al, 2018 ; Zhang et al, 2021d ; Somebang et al, 2021 ). Paradoxically, MAT2A and SOX4 were highly expressed in this cluster.…”
Section: Resultsmentioning
confidence: 99%
“…LPS (TLR4 ligand) and bacterial CpG-DNA (TLR9 agonist) are capable of inducing a functional interaction of NF-κB with the promoter element of HLA-DRA to induce MHC-II gene expression and of increasing CD86 expression in both a TLR4-dependent or TLR9-dependent manner. 37 39 Interestingly, neutralization of diS-HMGB1 increased expression of the immune checkpoint PD-L1 but TLR inhibition decreased its expression. TLR9 is reported to induce PD-L1 in dendritic cells (DCs), suggesting that TLR2, CXCR4, or another HMGB1 receptor not examined in this study competitively regulates myeloid PD-L1 to ultimately decrease its expression.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we found that the Gram-negative bacteria E. coli provides the strongest priming signal for human pDCs when compared to Gram-positive bacteria strains and the opportunistic fungi Candida albicans . However, similar to treatments with synthetic TLR ligands, E. coli alone did not induce mature IL-1β release, which is likely due to the fact that human pDCs, unlike mouse pDCs, do not express TLR4 [ 5 , 121 ].…”
Section: Discussionmentioning
confidence: 99%